Identifikasi molekuler Bakteri Asam Laktat dari Tempe dan Tape Berdasarkan Sekuen Gen 16S rRNA - Sulistiani Sulistiani; Iman Hidayat (Fakultas Biologi | Universitas Jenderal Soedirman, 2020)
Indonesia has varied of fermented food. However, the discovery of the microbial diversity in the Indonesian traditional fermented food is inadequately conducted. In this study, we determined the lactic acid bacteria (LAB) diversity from tempeh and tape based on the nucleotide sequence of 16S rRNA gene to obtain information on the biodiversity of lactic acid bacteria in tempeh and tape origin Bali Province, and collection of lactic acid bacteria isolates have beneficial for the development of starters, food science, and genetic resources. A total of six samples of tempeh and six samples of tape were collected from Bali province. A viable count method showed that the LAB population in tempeh was 3.8 x 108 – 2.2 x 109 cfu/g and in tape was 4 x 105 - 1.1 x 108 cfu/g. A molecular identification based on the nucleotide sequence of16S rRNA gene determined six LAB species existed in tempeh (Lactobacillus fermentum, L. plantarum, Enterococcus faecalis, E. faecium, Pediococcus pentosaceus, Weissella paramesenteroide) and six species in tape (L. fermentum, L. kunkeei, L. plantarum, L. vini, Leuconostoc mesenteroides, P. pentosaceus, W. paramesenteroides. Physiological characterization showed that all LAB isolates grew on medium containing 3% NaCl at pH 4 and pH 6.5, and at temperatures of 30°C and 45°C. Three isolates of P. pentosaceus (Su-ls21, Su-ls22, Su-ls24) exhibited catalase activity and 17 isolates belong to halotolerant bacteria, which can grow on medium containing 6.5% NaCl.